PEMBENTUKAN KARAKTER LEADERSHIP SANTRI MELALUI ORGANISASI MAKHIS DI MADRASAH MU’ALLIMIN HASYIM ASY’ARI TEBUIRENG JOMBANG - Abdul Hamid (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
This article aims at describing the establishment of student leadership roles and descriptions of MAKHIS in shaping the leadership roles of Madrasah Mu'allimin Hasyim Asy'ari Tebuireng Jombang. This type of research is qualitative. The research was conducted on the Head of Madrasah Mu'allimin Hasyim Asy'ari Tebuireng Jombang, Deputy Head of Student Affairs and Head of MAKHIS (Media Khidmah Santri) as informants. The data obtained are the results of observations, interviews and documentation which are then analyzed and concluded. Thus, the results of this study are: (1) MAKHIS (Media Khidmah Santri) Madrasah Mu'allimin Hasyim Asy'ari Tebuireng Jombang has work programs and activities that can shape the character of the Leadership of the Santri. One of the efforts to form student leadership character is by carrying out activities, because in these activities all administrators and members are involved to make the event a success, and by becoming a committee will form leadership character (2). The values contained in this MAKHIS organization are the values of sincere devotion or service. The leadership that Makhis wants to form is to form a leader figure who has qualities in religious scholarship, moral practice, and has a high spirit of devotion.